Methicillin-resistant Staphylococcus aureus in veterinary professionals in 2017 in the Czech Republic - Neradova, Katerina; Jakubu, Vladislav; Pomorska, Katarina; Zemlickova, Helena (BMC veterinary research, 2020)
BACKGROUND: Cases of colonization or infection caused by Methicillin-resistant Staphylococcus aureus (MRSA) are frequently reported in people who work with animals, including veterinary personnel. The aim of this study was to determine the prevalence of MRSA colonization among veterinary professionals. A total of 134 nasal swabs from healthy attendees of a veterinary conference held in the Czech Republic were tested for presence of MRSA. The stains were further genotypically and phenotypically characterized. RESULTS: Nine isolated MRSA strains were characterized with sequence type (ST), spa type (t) and Staphylococcal Cassette Chromosome mec type. Five different genotypes were described, including ST398-t011-IV (n = 5), ST398-t2330-IV (n = 1), ST398-t034-V (n = 1), ST225-t003-II (n = 1) and ST4894-t011-IV (n = 1). The carriage of the animal MRSA strain was confirmed in 8 cases, characteristics of one strain corresponded to the possible nosocomial origin. Among animal strains were described three spa types (t011, t034, t2330) belonging into one dominating clonal complex spa-CC11. CONCLUSION: According to our results, the prevalence of nasal carriage of MRSA in veterinary personnel is 6.72%. Although we described an increase compared to the results of previous study (year 2008), the prevalence in the Czech Republic is still remaining lower than reported from neighboring countries. Our results also indicate that healthcare - associated MRSA strains are still not spread among animals.
Keywords: Staphylococcal Infections; studium veterinárního lékařství; Occupational Exposure; přenašečství; Humans; nos; lidé středního věku; stafylokokové infekce; studenti; prevalence; Aged; dospělí; Methicillin-Resistant Staphylococcus aureus; Companion animals; senioři; lidé; Genotype; zvířata; Livestock; Adult; Carrier State; methicilin rezistentní Staphylococcus aureus; Middle Aged; pracovní expozice; Czech Republic; veterináři; Nose; Prevalence; genotyp; Education, Veterinary; Animals; Students; Česká republika; Carriage; Veterinarians; Livestock-associated MRSA